Sex, growth rate, rank order after brood reduction, and hatching date affect first‐year survival of long‐lived Herring Gulls. Issue 4 (11th November 2016) - Bosman, Davy S.; Stienen, Eric W. M.; Lens, Luc
Abstract: Among most species of birds, survival from hatching throughout the first year of life is generally lower than subsequent survival rates. Survival of young birds during their first year may depend on a combination of selection, learning, unpredictable resources, and environmental events (i.e., post‐fledging factors). However, knowledge about post‐fledging development in long‐lived species is usually limited due to a lengthy immature stage when individuals are generally unobservable. Therefore, pre‐fledging characteristics are often used to predict the survival of young birds. We assessed effects of nestling growth rates, hatching date, hatching asynchrony, brood size and rank order after brood reduction, and sex on first‐year survival of 137 fledglings using a mark‐resighting analysis. We found that the survival probability (Φ1yr = 0.39) of first‐year Herring Gulls ( Larus argentatus ) in our study colony located at the outer port of Zeebrugge (Belgium) was lower than that of older individuals (Φ>1yr = 0.75). All 10 models best supported by our data included nestling growth rate, suggesting that variability in first‐year survival may be linked primarily to individual variation in growth. First‐year survival was negatively correlated with hatching date and rank order after brood reduction. Hence, carry‐over effects of breeding season events such as timing of breeding, early development, and social status had an influence on survival of Herring Gulls after fledging. Furthermore, we found sex‐biased mortality in first‐year Herring Gulls, with females (Φ1yr = 0.45) surviving better than males (Φ1yr = 0.38). Although adult survival is generally regarded as the key parameter driving population trajectories in long‐lived species, juvenile survival has recently been acknowledged as an important source of variability in population growth rates. Thus, increasing our knowledge of factors affecting age‐specific survival rates is necessary to improve our understanding of population dynamics and ultimately life‐history variation.